Reform Practice of Vocational Curriculum: A Case Study of the "New Media Operations" Course - Wu Lisha; Liu Rong; Zhao Mengzhen (Journal of Exploration of Vocational Education, 2025)
In the digital era, the demand for professionals in new media operations has increased significantly. In response, Shandong Vocational College of Cultural Industries has carried out a reform of the "New Media Operations" course. Guided by the Outcome-Based Education (OBE) philosophy, the course content has been restructured and integrated with the "1+X" Media Convergence Certificate examination, realizing the integration of course learning and certification. Teaching effectiveness has been enhanced through the application of mind mapping and the Feynman technique. Students are also engaged in managing self-media accounts, with assessments based on both quantitative data and qualitative evaluation. The reform has yielded notable outcomes.